2011
DOI: 10.1128/aac.01732-10
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Sequence IS Aba11 Is Involved in Colistin Resistance and Loss of Lipopolysaccharide in Acinetobacter baumannii

Abstract: Infections caused by Acinetobacter baumannii are of increasing concern, largely due to the multidrug resistance of many strains. Here we show that insertion sequence ISAba11 movement can result in inactivation of the A. baumannii lipid A biosynthesis genes lpxA and lpxC, resulting in the complete loss of lipopolysaccharide production and high-level colistin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 11 publications
7
139
0
3
Order By: Relevance
“…Mutations in the pmrCAB operon, leading to increased production of the PmrAB system and modification of lipid A, have been identified in isolates of polymyxin-resistant A. baumannii (26,27). In addition, absence of lipid A in the cellular membrane, due to alterations in the lpx operon, has been found in laboratoryderived and clinical isolates of polymyxin-resistant A. baumannii (28,29). Corresponding findings have also been obtained for members of the Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 53%
“…Mutations in the pmrCAB operon, leading to increased production of the PmrAB system and modification of lipid A, have been identified in isolates of polymyxin-resistant A. baumannii (26,27). In addition, absence of lipid A in the cellular membrane, due to alterations in the lpx operon, has been found in laboratoryderived and clinical isolates of polymyxin-resistant A. baumannii (28,29). Corresponding findings have also been obtained for members of the Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 53%
“…Alterations in the lipid A biosynthesis genes (lpxA, lpxC, and lpxD) by amino acid substitutions, deletions, or insertion of ISAba1 are responsible for the loss of LPS [49,50]. A recent metabolomic study revealed that an LPS-deficient, colistin-resistant A. baumannii strain showed perturbation in specific amino acid and carbohydrate metabolites, particularly pentose phosphate pathway and TCA (tricarboxylic acid) cycle intermediates [37].…”
Section: Colistin Resistancementioning
confidence: 99%
“…Alteration of the charge status of LPS, for example, by 4-amino-4-deoxy-L-arabinose modification, is one well-studied mechanism of resistance (21). More recently, it was discovered that resistance to colistin in A. baumannii ATCC 19606 could be mediated by the complete loss of LPS, in turn revealing that LPS is not essential in this organism, at least under typical in vitro growth conditions (22)(23)(24). This observation extended data from previous reports that LPS is not essential in certain other Gram-negative organisms (25)(26)(27).…”
mentioning
confidence: 99%